2015
DOI: 10.4238/2015.june.11.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous 5-aminolevulinic acid on photosynthesis, stomatal conductance, transpiration rate, and PIP gene expression of tomato seedlings subject to salinity stress

Abstract: ABSTRACT. The effects of exogenous 5-aminolevulinic acid (ALA) on photosynthesis, plant growth, and the expression of two aquaporin genes in tomato seedlings under control and salinity conditions were investigated. Exogenous ALA application significantly improved net photosynthetic rate (P n ), total chlorophyll content, and plant biomass accumulation of tomato seedlings under salinity stress. As revealed by real-time PCR analyses, after treatment with ALA alone, expression of both LePIP1 and LePIP2 in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Leaf water-retention capacity is strongly related to the stomatal conductance and transpiration rate in plants4950. Under stress conditions, our results indicated significantly higher stomatal conductance and transpiration rate in ShCML44 overexpressing lines than that of wild-type plants (Figs 5b,d and 8b,d).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Leaf water-retention capacity is strongly related to the stomatal conductance and transpiration rate in plants4950. Under stress conditions, our results indicated significantly higher stomatal conductance and transpiration rate in ShCML44 overexpressing lines than that of wild-type plants (Figs 5b,d and 8b,d).…”
Section: Discussionmentioning
confidence: 53%
“…Stomatal conductance and transpiration rate contribute to improving photosynthesis and intercellular CO 2 concentration rate51, our findings demonstrated significantly higher activity of photosynthesis and intercellular CO 2 rate in transgenic plants compared to wild-type in stress conditions (Figs 5a,c and 8a,c). Furthermore, higher gas exchange attributes play a critical role to improve relative water content by higher root water uptake50. Under drought conditions, our findings showed lower leaf water loss rate and improved RWC in transgenic plants than the wild-type (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Because of the predominantly protective effect of ALA against environmental stress, its mechanism has increasingly gained attention. According to the existing evidence, the exogenous application of ALA increases the chlorophyll content, activates antioxidant enzymes, reduces lipid peroxidation of the membrane [13], promotes photosynthesis [15], enhances the tetrapyrrole biosynthetic pathway and proline accumulation [14], improves the metabolism of polyamines [17], regulates nitrogen metabolism, absorption, aggregation and distribution of nutrient ions [22,25], inhibits the microstructural damage in chloroplasts by increasing the proportion of intact thylakoids [26], and regulates the expression of genes [27]. Our previous study showed that ALA pretreatment enhanced the photosynthetic capacity of droughtstressed wheat seedlings [23], but the regulatory mechanism behind this effect is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…ALA also improved root growth of cucumber (Cucumis sativus L.) (Zhen et al 2012), Swiss chard (Beta vulgaris L. subsp. cicla) (Liu et al 2014), rice (Oryza sativa) (Nunkaew et al 2014), and tomato (Solanum lycopersicum) (Zhao et al 2015) seedlings under NaCl stress. Moreover, ALA enhanced root growth of spring wheat (Triticum aestivum L.) (Kosar et al 2015), oilseed rape (Brassica napus L.) (Liu et al 2016), and Arabidopsis (An et al 2016c) under water deficit condition.…”
Section: Introductionmentioning
confidence: 99%